2017
DOI: 10.24263/2304-974x-2017-6-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adding of laurel essential oil extracts on salad dressings properties

Abstract: Keywords:Laurel Leaves Extracts Chemical Composition Salad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ash content was determined by AOCS (method Ba 5a-49) [14]. Moisture content measurement was done by drying up to constant weight at 105 °C [15].…”
Section: Physicochemical Analysis Of Seed and Oil Seed Characteristicmentioning
confidence: 99%
“…Ash content was determined by AOCS (method Ba 5a-49) [14]. Moisture content measurement was done by drying up to constant weight at 105 °C [15].…”
Section: Physicochemical Analysis Of Seed and Oil Seed Characteristicmentioning
confidence: 99%
“…It has been reported that nanomats containing nisin and curcumin were able to delay the sensory deterioration in fish samples stored at 4 °C . It has also been stated that sensory acceptability in the salad dressings with extracts from humid laurel leaves was defined as higher as compared to the control stored at 10 °C . In addition, the leaves are defined as characteristically fragrant once crushed yet taste bitter and aromatic as stated by Bagchi and Srivastava .…”
Section: Resultsmentioning
confidence: 99%
“…44 It has also been stated that sensory acceptability in the salad dressings with extracts from humid laurel leaves was defined as higher as compared to the control stored at 10 °C. 55 In addition, the leaves are defined as characteristically fragrant once crushed yet taste bitter and aromatic as stated by Bagchi and Srivastava. 56 In the present study, especially the odor parameter in the cooked fish samples coated with LZn was significantly high (p < 0.05).…”
Section: Color Stabilitymentioning
confidence: 99%